2008
DOI: 10.1111/j.1440-1754.2007.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of adolescents on overweight and obesity: The weight of opinion study

Abstract: Aim:The incidence and prevalence of overweight and obesity are rising around the world. Health promotion planning must be informed by the knowledge, perceptions, motivations and perceived needs of the target population, but little is known about how adolescents perceive overweight and obesity, its causes and solutions. Methods: A cross-sectional, non-representative sample of 12-to 17-year-old boys and girls (n = 58) attending schools in diverse metropolitan areas and one rural area in NSW, Australia. Focus gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 3 publications
2
46
0
Order By: Relevance
“…Indeed, many overweight individuals express a desire to limit their food consumption, yet struggle to control their intake and repeatedly consume past energy requirements 7, 8. Development of feeding behavior that is insensitive to negative outcome is analogous to the compulsive drug-taking behavior seen in human drug addicts that is similarly impervious to negative consequences 9.…”
mentioning
confidence: 99%
“…Indeed, many overweight individuals express a desire to limit their food consumption, yet struggle to control their intake and repeatedly consume past energy requirements 7, 8. Development of feeding behavior that is insensitive to negative outcome is analogous to the compulsive drug-taking behavior seen in human drug addicts that is similarly impervious to negative consequences 9.…”
mentioning
confidence: 99%
“…Stood out as crucial for the children's choice of fruit and vegetables in studies from different country settings [16,29,32,33,38,43-45,49]. Negative aspects of appearance were unripe, mouldy, rotten, wrinkled, "looks horrible", "looks weird", ugly, soggy, and boring.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of affordability was highlighted in ten studies that indicated that price influenced children's purchases and selection of fruit and vegetables in all country settings [25,27,28,32-35,44-46,49,50]. The study by Hill et al (1998) from New Zealand suggested that children's primary shopping criterion was quantity, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations